Qualitative Research as Social Justice Practice with Culturally Diverse Populations - Heather Z. Lyons; Denise H. Bike; Lizette Ojeda; Adanna Johnson; Rocío Rosales; Lisa Y. Flores (Journal for Social Action in Counseling and Psychology)
The qualitative research process can offer counselors and psychologists the opportunity to participate in social justice practice. Qualitative research contributes to social justice when researchers promote the following principles: equity, access, participation, and harmony for culturally diverse populations, those currently most at risk for acts of social injustice. In this manuscript we suggests ways in which qualitative approaches can provide a vehicle by which social justice can be enacted when researchers are conscious and deliberate about these intentions. To this end, we review and highlight best practices in socially just qualitative research processes across the following aspects of research: design, data collection, data analysis and interpretation, and application of findings.